State-of-the-art review on low-velocity impact response of reinforced concrete beams - Adhikary, Satadru Das (2017)
Based on a comprehensive literature review, a state-of-the-art report on the strain rate dependent mechanical properties of materials involved in reinforced concrete (RC) structures and the structural response of RC beams under low-velocity impact is presented. Due to the prevalence of plentiful equations to calculate the dynamic increase factor of concrete strength in compression and tension, future research is needed to reach a general consensus. Two empirical equations were derived based on previous test data, and the applicability of the proposed equations is demonstrated. With the interpretation of previous data in the light of authors' test results, the issue related to a change in failure mode from flexural failure under static loading to shear failure under impact loading is discussed. Finally, several issues related to the impact response of beams are raised, and the need for future research is identified.